DEVELOPING COMMUNITY SKILL IN READING KITAB THROUGH AL FATIH READING METHOD TRAINING - Firda Ayu (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2022)
Reading is one of the receptive processes as way to take the information. Reading becomes difficult when related to the literature which is asked the special skill in reading and interpreting those literature. One of this literature is called kitab kuning. Kitab kuning is one of the islamic literature which is contained of some materials, such as fiqih, hadits and tafsir. This literature also usually written in Arabic with no specific symbols (fathah, dhammah, kasrah or sukun). One of the methods in reading kitab kuning which can be taught is called Al Fatih. Al Fatih method gives an advantage for the readers of kitab kuning because of this method has special portion in learning nahwu sharraf, therefore we have not to learn that comprehensively. Through empowerment program with ABCD (Asset-Based Community Development), is specially hoped could increase community’s knowledge specially student of pesantren as we called santri about reading kitab kuning. There are 3 ways which are conducted in order to develop community’s skill in reading kitab kuning, those are: spread out the method of reading kitab kuning through Al Fatih method to the students/ santri of islamic institution,  conducted ToT or Training of Trainer, the last is designate the tutor in every islamic institution.